(untitled) (Perner’s Contacts, 2016)
This article discusses transport network elements vulnerability identification using methods of multicriteria decision-making. For the purpose of the vulnerability determining the method AHP (Analytic Hierarchy Process) was used. This method is applied to real sections of road of the Slovak Republic. The individual sections are assessed based on selected criteria and principles of the chosen method.